Vulcano: A new robotic challenge for legged robots - Domingos, Manuel; Pedro, Francisco; Ramos, Alberto; Funk, Matthias G.; Mendes, Armando; Cascalho, José (Frontiers in Robotics and AI, 2023)
Vulcano Challenge is a new and innovative robotic challenge for legged robots in a physical and simulated scenarios of a volcanic eruption. In this scenario, robots must climb a volcano’s escarpment and collect data from areas with high temperatures and toxic gases. This paper presents the main idea behind this challenge, with a detailed description of the simulated and the physical scenario of the volcano ramp, the rules proposed for the competition and the conception of a robot prototype dubbed Vulcano used in the competition. Finally, it discusses the performance of teams invited to participate in the challenge in the context of Azorean Robotics Open, the Azoresbot 2022. This first test for this challenge provided insights into what the participants found exciting and positive, and what they found less positive.